Respuesta :
After a small search, I've found that we want to find the inverses of both functions. We will find that E(x) does not have an inverse function, and the inverse function of T(x) is h(x) = x/6 - 1/6
Here we have a piecewise function:
T(x) = 6(x-3) + 25 if x > 3
E(x) = 25 if 0 ≤ x ≤ 3
First, remember that two functions f(x) and g(x) are inverses if:
f(g(x)) = x
g(f(x)) = x
From that definition we can see that E(x) does not have an inverse, because for any function g(x), we will have:
E(g(x)) = 25
So E(x) can't meet the condition.
Now let's analyze the function T(x)
T(x) = 6(x-3) + 25
We can rewrite it as:
T(x) = 6x - 6×3 + 25
T(x) = 6x + 1
Note that T(x) is a linear equation, so the inverse will also be a linear equation. Let's assume that the inverse is h(x) = ax + b
We will have:
T(h(x)) = 6×h(x) + 1 = 6(ax + b) + 1
Now, if these are inverses, we have:
6(ax + b) + 1 = x
6ax + 6b + 1 = x
Then we must have:
6b + 1 = 0
6ax = x
From the first equation, we can get:
6b + 1 = 0
6b = -1
b = -1/6
From the second equation we have:
6ax = x
6a = 1
a = 1/6
Then:
h(x) = x/6 - 1/6
And this is the inverse function of T(x)
If you want to learn more, you can read:
https://brainly.com/question/10300045